Trichoptera and Plecoptera of the Seybouse River, northeast Algeria: Distribution, phenology and new records - Samraoui, Boudjéma; Bouhala, Zineb; Garcia, Antonio Ruiz; Márquez-Rodríguez, Joaquín; Ferreras-Romero, Manuel; El-Serehy, Hamed A.; Samraoui, Farrah (Zootaxa, 2020)
The stoneflies and caddisflies of North Africa are still poorly known as vast areas of Algeria have yet to be investigated. A survey of the macroinvertebrates of the Seybouse River, northeast Algeria, was carried out from July 2014 to December 2016. Three species of stoneflies (Capnopsis schilleri, Capnioneura petitpierreae, and Tyrrhenoleuctra tangerina) and five taxa of caddisflies (Mesophylax aspersus, Hydropsyche maroccana, H. resmineda, H. artax/lobata, and H. gr. pellucidula) were identified. All taxa are new records to the Seybouse River and seven of them are new to northeastern Algeria. A multivariate analysis indicated that the Hydropsychidae exhibited a clear longitudinal gradient along the Seybouse River while Mesophylax aspersus seemed adapted to species-poor, intermittent streams. Further investigations of the stoneflies and caddisflies may inform conservation efforts and will prove useful to monitor the Seybouse River and similarly threatened North African rivers and streams.